Scoping review to evaluate existing measurement parameters and clinical outcomes of transtibial prosthetic alignment and socket fit. Issue 2 (14th April 2022) - Won, Nae Yeon; Paul, Alexandra; Garibaldi, Matthew; Baumgartner, Rita E.; Kaufman, Kenton R.; Reider, Lisa; Wrigley, Jordan; Morshed, Saam
Abstract : Introduction: Fit and alignment are observable objectives of the prosthesis rendering process for individuals with lower limb amputation. Nevertheless, there is a dearth of validated measures to directly assess the quality of this clinical procedure. Objectives: The objectives of this scoping review are to evaluate existing measurement parameters and clinical outcomes used in investigations of transtibial socket fit or prosthetic alignment and to identify gaps in the literature regarding tools for evaluation of prosthetic fitting. Study design: Scoping literature review. Methods: A comprehensive search was conducted in the following databases: MEDLINE (through PubMed), Embase (through Elsevier), Scopus (through Elsevier), and Engineering Village (through Elsevier), resulting in 6107 studies to be screened. Results: Sixty-three studies were included in the review. When measuring fit, studies most frequently reported on patient-reported comfort (n = 22) and socket size compared with the residual limb volume (n = 9). Alignment was most frequently measured by the prosthetists' judgment and/or use of an alignment jig (n = 34). The measurement parameters used to determine alignment or fit varied greatly among the included studies. Conclusion: This review demonstrated that most measures of socket fit rely on a patient's self-report and may vary with biopsychosocial factors unrelated to the socket fitting process. Meanwhile, alignment is determined mostly by the prosthetist's judgment, paired with objective measurements, such as alignment jigs and gait analysis. Efforts to standardize and validate measures of these parameters of prosthetic fitting are vital to improving clinical practice and reporting outcomes.